2007
DOI: 10.1179/174328407x226626
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between substrate steel texture and coating texture of two industrially produced galvanised and galvannealed steels

Abstract: The substrate steel texture appears to control the texture of galvanised and galvannealed coating on steels. The ratio of the volume fraction of {113} and {111} orientations of the substrate steel may be important in controlling the texture of the overlying coating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The orientation distributions for the Zn phase in the defect region are mostly concentrated along the basal fiber {0002} buvtwN. This kind of texture is normally encountered in galvanized coatings on steels [17]. Therefore, it appears that part of the coating over the defect region is close to galvanized coating, although the simultaneous presence of δ clearly indicates that partial alloying of Zn with Fe has also taken place.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The orientation distributions for the Zn phase in the defect region are mostly concentrated along the basal fiber {0002} buvtwN. This kind of texture is normally encountered in galvanized coatings on steels [17]. Therefore, it appears that part of the coating over the defect region is close to galvanized coating, although the simultaneous presence of δ clearly indicates that partial alloying of Zn with Fe has also taken place.…”
Section: Resultsmentioning
confidence: 93%
“…The textures of the δ phase from both the defect and the defect free regions of the coating show the presence of a strong fiber of the type 01 1 − 3 n o buvtwN. Chakraborty and Ray [17] have reported that the above kind of texture fiber is beneficial for the enhancement of the powdering resistance of galvannealed coatings. The basal planes are the primary slip planes in the hexagonal δ phase.…”
Section: Resultsmentioning
confidence: 96%